Karykatura jugosłowiańskiej rzeczywistości – Nowe szaty cesarza Ante Babai - Putyńska, Urszula (Przestrzenie Teorii, 2024)
This article aims to analyze The Emperor’s New Clothes (1961), the first feature movie by Ante Babaja. The director employed his vivid literary imagination to retell the classic fairy tale by Hans Christian Andersen. Babaja’s theoretical self-awareness, his deep understanding of the very process of adapting literature, enabled him to create a layered allegory of Yugoslavia under the rule of Josip Broz-Tito.